Expression quantitative trait loci of genes predicting outcome are associated with survival of multiple myeloma patients. Issue 2 (30th March 2021) - Macauda, Angelica; Piredda, Chiara; Clay‐Gilmour, Alyssa I.; Sainz, Juan; Buda, Gabriele; Markiewicz, Miroslaw; Barington, Torben; Ziv, Elad; Hildebrandt, Michelle A. T.; Belachew, Alem A.; Varkonyi, Judit; Prejzner, Witold; et al.
Abstract: Gene expression profiling can be used for predicting survival in multiple myeloma (MM) and identifying patients who will benefit from particular types of therapy. Some germline single nucleotide polymorphisms (SNPs) act as expression quantitative trait loci (eQTLs) showing strong associations with gene expression levels. We performed an association study to test whether eQTLs of genes reported to be associated with prognosis of MM patients are directly associated with measures of adverse outcome. Using the genotype‐tissue expression portal, we identified a total of 16 candidate genes with at least one eQTL SNP associated with their expression with P < 10 −7 either in EBV‐transformed B‐lymphocytes or whole blood. We genotyped the resulting 22 SNPs in 1327 MM cases from the International Multiple Myeloma rESEarch (IMMEnSE) consortium and examined their association with overall survival (OS) and progression‐free survival (PFS), adjusting for age, sex, country of origin and disease stage. Three polymorphisms in two genes ( TBRG4 ‐rs1992292, TBRG4 ‐rs2287535 and ENTPD1 ‐rs2153913) showed associations with OS at P < .05, with the former two also associated with PFS. The associations of two polymorphisms in TBRG4 with OS were replicated in 1277 MM cases from the International Lymphoma Epidemiology (InterLymph) Consortium. A meta‐analysis of the data from IMMEnSE and InterLymph (2579 cases) showed that TBRG4 ‐rs1992292 is associated with OS (hazard ratio = 1.14, 95% confidence interval 1.04‐1.26, P = .007). In conclusion, we found biologically a plausible association between a SNP in TBRG4 and OS of MM patients. Abstract : What's new? Multiple myeloma (MM) remains incurable for most patients, although recent therapeutic advances have extended survival. MM is highly heterogeneous, but gene expression profiling can identify patients with poor outcomes and classify patients by how they will respond to drugs. Here, the authors evaluate certain genetic loci that influence the amount of RNA transcript produced, called expression quantitative trait loci (eQTLs). They found two eQTLs of genes associated with MM prognosis that were directly associated with adverse outcomes. These results provide a proof‐of‐concept that eQTLs can serve as a surrogate for gene expression profile as a predictor of survival, and they are much easier to measure.